Evaluating the impact of a rapid response system on survival of patients with cancer undergoing emergency surgery for acute abdomen: A single-center retrospective cohort study - Jae Hoon Lee; Sang Yun Jung; Ki Ho Yu; Mee Hee Shin; Yun Jung Choi; Ra Mi Choi; Woo Jin Seo; Sang Hee Park; Won Ho Han (PLoS ONE, 2026)
Patients with cancer who develop acute abdomen are at high risk of rapid clinical deterioration and often require emergency surgery and intensive care. This retrospective cohort study evaluated the impact of implementing a Rapid Response System (RRS) on survival among 274 patients admitted for emergency surgery at a tertiary cancer center in Korea (145 pre-RRS, 129 post-RRS). Although the post-RRS group had a higher burden of severe illness, including more metastatic disease and higher APACHE II scores, key time intervals from diagnosis to ICU admission, surgery, and antibiotic administration were significantly shorter following RRS implementation. The post-RRS group also demonstrated more favorable postoperative physiological trajectories, including lower postoperative day 7 SOFA scores and greater reductions in SOFA from baseline. Survival to discharge was higher after RRS implementation (85.27% vs. 74.48%, p = 0.039), and RRS activation remained independently associated with improved survival in multivariable analysis (adjusted odds ratio: 3.554, p = 0.021). Patients presenting outside RRS coverage hours had higher severity, longer delays to intervention, and lower survival; in an exploratory counterfactual model, predicted survival increased from 59.4% to 71.0% when RRS availability was hypothetically extended. These findings suggest that RRS implementation may attenuate progression of organ dysfunction and improve survival among high-risk cancer patients with acute abdomen. Expanding RRS operational hours, including continuous 24-hour coverage, may offer additional clinical benefit.